Evolution within a given virulence phenotype (pathotype) is driven by changes in aggressiveness: a case study of French wheat leaf rust populations - Fontyn, Cécilia; Meyer, Kevin JG; Boixel, Anne-Lise; Delestre, Ghislain; Piaget, Emma; Picard, Corentin; Suffert, Frédéric; Marcel, Thierry C; Goyeau, Henriette (Peer Community Journal)

(untitled)
Plant pathogens are constantly evolving and adapting to their environment, including their host. Virulence alleles emerge, and then increase, and sometimes decrease in frequency within pathogen populations in response to the fluctuating selection pressures imposed by the deployment of resistance genes. In some cases, these strong selection pressures cannot fully explain the evolution observed in pathogen populations. A previous study on the French population of Puccinia triticina, the causal agent of wheat leaf rust, showed that two major pathotypes — groups of isolates with a particular combination of virulences — predominated but then declined over the 2005-2016 period. The relative dynamics and the domination of these two pathotypes — 166 317 0 and 106 314 0 —, relative to the other pathotypes present in the population at a low frequency although compatible, i.e. virulent on several varieties deployed, could not be explained solely by the frequency of Lr genes in the landscape. Within these two pathotypes, we identified two main genotypes that emerged in succession. We assessed three components of aggressiveness — infection efficiency, latency period and sporulation capacity — for 44 isolates representative of the four P. triticina pathotype-genotype combinations. We showed, for both pathotypes, that the more recent genotypes were more aggressive than the older ones. Our findings were highly consistent for the various components of aggressiveness for pathotype 166 317 0 grown on Michigan Amber — a ‘naive’ cultivar never grown in the landscape — or on Apache — a ‘neutral’ cultivar, which does not affect the pathotype frequency in the landscape and therefore was postulated to have no or minor selection effect on the population composition. For pathotype 106 314 0, the most recent genotype had a shorter latency period on several of the cultivars most frequently grown in the landscape, but not on ‘neutral’ and ‘naive’ cultivars. We conclude that the quantitative components of aggressiveness can be significant drivers of evolution in pathogen populations. A gain in aggressiveness stopped the decline in frequency of a pathotype, and subsequently allowed an increase in frequency of this pathotype in the pathogen population, providing evidence that adaptation to a changing varietal landscape not only affects virulence but can also lead to changes in aggressiveness.